Study on fast charger for 5V 1500F supercapacitor module from photovoltaic panel - Tung, Doan Thanh; Dung, Hoang Tran; Lu, Le Trong (Vietnam Journal of Science and Technology, 2019)
Supercapacitor can be used for energy storage and peak power control in order to increase the efficiency and the life cycle of the system. Energy storage systems or energy buffers using supercapacitor for solar energy systems have been presented in many recent studies. However, fast-charging process for supercapacitor from photovoltaic (PV) is mentioned very little. In this paper, the fast-charging system is designed with limited current control algorithms. This charger can protect 5V 1500F supercapacitor module and 100W PV panel safely. The experiment results under various solar irradiance intensity conditions is described by the characteristics of voltage and current.